2009
DOI: 10.1002/qj.421
|View full text |Cite
|
Sign up to set email alerts
|

Infrasound generation by tornadic supercell storms

Abstract: Acoustic wave generation by turbulence in a stratified, moist atmosphere is studied. It is shown that, in saturated moist air turbulence, in addition to the Lighthill's quadrupole and dipole sources of sound (related to stratification and temperature fluctuations), there exist monopole sources related to heat and mass production during the condensation of moisture. We determine the acoustic power of these monopole sources and show that this radiation is dominant for typical parameters of strong convective stor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Recent simulations (Schecter & Nicholls, 2010;Schecter, 2012) show that there is a lack of discernible infrasound in the absence of latent-heating effects and that non-tornadic thunderstorm cells produce infrasound from the melting level. This suggests that latent heat sources are a likely mechanism, and simulations of the liquid-vapor transitions within a cloud were able to produce infrasound between 0.1 and 10 Hz (Akhalkatsi & Gogoberidze, 2009;Schecter & Nicholls, 2010). However, radial vortex oscillations including the non-columnar nature of a tornado (Schecter, 2012) and analysis incorporating nonequilibrium effects (Zuckerwar & Ash, 2006;Ash et al, 2011) are also consistent with observations.…”
Section: B Comparison With Potential Mechanismsmentioning
confidence: 57%
“…Recent simulations (Schecter & Nicholls, 2010;Schecter, 2012) show that there is a lack of discernible infrasound in the absence of latent-heating effects and that non-tornadic thunderstorm cells produce infrasound from the melting level. This suggests that latent heat sources are a likely mechanism, and simulations of the liquid-vapor transitions within a cloud were able to produce infrasound between 0.1 and 10 Hz (Akhalkatsi & Gogoberidze, 2009;Schecter & Nicholls, 2010). However, radial vortex oscillations including the non-columnar nature of a tornado (Schecter, 2012) and analysis incorporating nonequilibrium effects (Zuckerwar & Ash, 2006;Ash et al, 2011) are also consistent with observations.…”
Section: B Comparison With Potential Mechanismsmentioning
confidence: 57%
“…(16) represent well known sources of sound: the first term represents Lighthill's quadrupole source (Lighthill, 1952); the second term is a dipole source related to temperature fluctuations (Goldstein, 1976); S γ is a monopole source related to variability of adiabatic index and usually has negligible acoustic output (Howe, 2001). As it was shown in Akhalkatsi and Gogoberidze (2009), in the case of saturated moist air turbulence there exists two additional monopole sources of sound, S q and S m , related to nonstationary heat and mass production during condensation of moisture, respectively.…”
Section: General Formalismmentioning
confidence: 92%
“…As shown by Akhalkatsi and Gogoberidze (2009), the peak frequency of acoustic radiation is inversely proportional to the turnover time of energy containing turbulent eddies ν peak ∼ v 0 /l, whereas total acoustic power is proportional to v 4 0 , ∆T 4 and inversely proportional to l.…”
Section: Spectral Decompositionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, entropy and mass fluctuations associated with phase transitions may also contribute. A recent analytical study concluded that such fluctuations in the moist turbulence of a severe storm are likely to dominate other sources of 0.1-Hz infrasound (Akhalkatsi and Gogoberidze 2009).…”
Section: Introductionmentioning
confidence: 98%